Exploring chilling stress and recovery dynamics in C4 perennial grass of Miscanthus sinensis - Karolina Sobańska; Monika Mokrzycka; Martyna Przewoźnik; Tomasz Pniewski; Katarzyna Głowacka (PLoS ONE, 2025)
The increasing cultivation of perennial C4 grass known as Miscanthus spp. for biomass production holds promise as a sustainable source of renewable energy. Unlike the sterile triploid hybrid of M. × giganteus, which cannot reproduce through seeds, M. sinensis possesses attributes that could potentially address these limitations by effectively establishing itself through seed propagation. This study aimed to investigate how 18 genotypes of M. sinensis respond to chilling stress and subsequent recovery. Various traits were measured, including growth and biomass yield, the rate of leaf elongation, and a variety of chlorophyll fluorescence parameters, as well as chlorophyll content estimated using the SPAD method. Principal Component Analysis revealed unique genotype responses to chilling stress, with distinct clusters emerging during the recovery phase. Strong, positive correlations were identified between biomass content and yield-related traits, particularly leaf length. Leaf growth analysis delineated two subsets of genotypes: those maintaining growth and those exhibiting significant reductions under chilling conditions. The Comprehensive Total Chill Stress Response Index (SRI) pinpointed highly tolerant genotypes such as Ms16, Ms14, and Ms9, while Ms12 showed relatively lower tolerance.